CRITICAL ANALYSIS OF UBIQUITOUS COMPUTING BASED ON MARTIN HEIDEGGER‘S NOTIONS OF WORLD AND TECHNOLOGY - Christ, Oliver (European Scientific Journal, ESJ, 2015)
The development of modern technology, in particular information and communication technology has caused the relationship between mankind and reality to fundamentally change. Ubiquitous computing designates a vision of an informationalized world, in which everyday objects are modified through computer technology such as RFID, sensors and sensor systems, tracking systems, or small computer units, giving them additional information or functions and integrating them with their environment. This paper explores the phenomenon of ubiquitous computing by applying some of the key concepts found in the philosophical works of Martin Heidegger and conducts a critical analysis using Martin Heidegger’s reflections on “world” and “technology” from Sein und Zeit (Being and Time) of 1957, and from the paper “Die Frage nach der Technik” (“The Question Concerning Technology”). The concept of “Ge-stell” introduced by Martin Heidegger to the philosophy of technology describes the situation of mankind and technology in a world shaped by modern technology. Both, mankind and technology, are tied together within the same world. The world has been shaped and redesigned by technology, and the individual is completely tied into the technologized world.